2007
DOI: 10.1007/s00421-007-0462-3
|View full text |Cite
|
Sign up to set email alerts
|

Force enhancement during and following muscle stretch of maximal voluntarily activated human quadriceps femoris

Abstract: Force enhancement during and following muscle stretch has been observed for electrically and voluntarily activated human muscle. However, especially for voluntary contractions, the latter observation has only been made for adductor pollicis and the ankle joint muscles, but not for large muscles like quadriceps femoris. Therefore, the aim of this study was to investigate the effects of active muscle stretch on force production for maximal voluntary contractions of in vivo human quadriceps femoris (n = 15). Peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
81
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(97 citation statements)
references
References 36 publications
9
81
7
Order By: Relevance
“…It has been well documented that the steady-state isometric force after active stretching is enhanced compared with the corresponding purely isometric reference contractions (Abbott and Aubert, 1952;Edman et al, 1978;Hahn et al, 2007;Herzog and Leonard, 2002;Joumaa et al, 2008a;Minozzo et al, 2013;Pinniger et al, 2006). This phenomenon is called residual force enhancement.…”
Section: Discussionmentioning
confidence: 97%
“…It has been well documented that the steady-state isometric force after active stretching is enhanced compared with the corresponding purely isometric reference contractions (Abbott and Aubert, 1952;Edman et al, 1978;Hahn et al, 2007;Herzog and Leonard, 2002;Joumaa et al, 2008a;Minozzo et al, 2013;Pinniger et al, 2006). This phenomenon is called residual force enhancement.…”
Section: Discussionmentioning
confidence: 97%
“…Pinniger and Cresswell (2007) found RFE during submaximal voluntary contractions in the plantar-and dorsiXexor groups, while Hahn et al (2007) did not Wnd RFE in maximally activated human quadriceps femoris. Hahn et al (2007) also reported that peak torques during stretch did not occur at the end of the stretch. This is in contrast to previous experiments on stimulated (Fig.…”
Section: Introductionmentioning
confidence: 93%
“…3 in Lee and Herzog 2002). Furthermore, Hahn et al (2007) reported that muscle activation was signiWcantly reduced during and after stretching. They speculated that the lack of RFE might be due to the size of the tested muscle (m. quadriceps compared to plantar and dorsiXexors or adductor pollicis in previous studies).…”
Section: Introductionmentioning
confidence: 96%
“…This association is independent of the coupling of new cross bridges actin -myosin that remains after ceased the stimulus (7,17,22,28,33,97).…”
Section: Elastic Components In Parallel Recruitment Theorymentioning
confidence: 94%
“…Another important aspect is that recent studies have observed the manifestation of FD and FE in higher muscle groups and motor gestures more similar to human routine, both in maximal voluntary and submaximal force exertions (27,28,29,30,31). It is noteworthy that although there are many studies proving the existence of FD and FE as well as some hypotheses to explain such behaviors has been raised, no theory is fully accepted to explain such behaviors.…”
Section: The Concept Of Force Depressionmentioning
confidence: 99%